Radiofrequency ablation for treatment of locally recurrent thyroid cancer presenting as a metastatic lymph node with dense macrocalcification: A case report and literature review. Issue 9 (March 2018) - Yoo, Roh-Eul; Kim, Ji-hoon; Paeng, Jin Chul; Park, Young Joo
Abstract: Rationale: Long-term recurrence rate of differentiated thyroid carcinoma has been reported to be as high as 30%. Repeat surgery may be challenging due to normal tissue plane distortion secondary to postoperative fibrosis, especially for small-sized recurrences. Recently, radiofrequency ablation (RFA) has been suggested to be a safe and effective alternative for high-risk patients or those who refuse surgery. Nonetheless, the efficacy of RFA remains questionable for densely calcified lymph nodes, which would have an increased likelihood of leaving residues after RFA. Patient concerns: We present a case of a successful combined treatment of a metastatic lymph node with dense macrocalcification with the use of a single RFA session and radioactive iodine (RAI) ablation in a patient with a previous history of total thyroidectomy and neck node dissection for papillary thyroid carcinoma. Diagnoses: A 71-year-old man with papillary thyroid carcinoma underwent total thyroidectomy and neck node dissection followed by RAI ablation. The stimulated serum thyroglobulin level was 4.74 ng/mL at the time of RAI ablation, and the follow-up ultrasonography 3 months later revealed a 15-mm lymph node with dense macrocalcification at the right cervical level III. Interventions: After confirming metastasis on cytology, the lesion was treated with ultrasound-guided RFA. Outcomes: The single RFA session combined with RAI ablation led to biochemical remission at 5 months after RFA, and complete resolution of structural recurrence including macrocalcification was observed 7 months after the second RAI (1 year after RFA). The patient remained free of recurrence at the 5-year follow-up. Lessons: RFA may offer a safe and effective alternative to 'berry picking' surgery in cases of surgical ineligibility or patient refusal of surgery even when the target lesions contain dense macrocalcification.